2020
DOI: 10.1097/jsa.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Capsular Management Techniques and Hip Arthroscopy

Abstract: There has been an increased emphasis on capsular management during hip arthroscopy in the literature in recent years. The capsule plays a significant role in the hip joint stability and studies have demonstrated that capsular closure can restore the biomechanics of the hip back to the native state. Capsular management also affects functional outcomes with capsular repair resulting in better clinical outcomes in some studies. Management of the capsule has evolved in recent years with more surgeons performing ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The overall number of hip arthroscopies performed worldwide has surged in the last decade [4,15]. The surge is due not only to the increased familiarity with the technique and the equipment but also to the awareness that pathologies around the hip joint have gained [16,17]. A painful hip is most commonly a result of femoroacetabular impingement syndrome (FAS), labral tears, snapping hip syndrome, osteoarthritis, synovitis, a loose body, or septic arthritis [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall number of hip arthroscopies performed worldwide has surged in the last decade [4,15]. The surge is due not only to the increased familiarity with the technique and the equipment but also to the awareness that pathologies around the hip joint have gained [16,17]. A painful hip is most commonly a result of femoroacetabular impingement syndrome (FAS), labral tears, snapping hip syndrome, osteoarthritis, synovitis, a loose body, or septic arthritis [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The surge is due not only to the increased familiarity with the technique and the equipment but also to the awareness that pathologies around the hip joint have gained [16,17]. A painful hip is most commonly a result of femoroacetabular impingement syndrome (FAS), labral tears, snapping hip syndrome, osteoarthritis, synovitis, a loose body, or septic arthritis [17,18]. Open procedures have been replaced by less invasive arthroscopic interventions and a recent systematic review by Kyin et al [18] reported considerable improvement in patient-reported outcomes in the mid-to long term.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were recruited from a single surgeon's high‐volume hip preservation clinical practice (Shane J. Nho). To be selected for this particular study, all participants had to meet the following criteria: be diagnosed with cam‐type FAIS based on clinical examination, have radiographic evidence of alpha angle >50 $\gt 5{0}^{\circ }$, be scheduled to undergo hip arthroscopic surgery with a planned surgical resection of the proximal femur to remove the cam morphology, and be scheduled to undergo both preoperative and postoperative 1.5T MRI (Figure 1[1]) 49–52 . Exclusion criteria for the study included: radiographic evidence of Tönnis Grade >1 $\gt 1$ hip osteoarthritis (OA), history of prior surgery to the index or contralateral hip, and history of a developmental hip disorder such as Legg‐Calvé‐Perthes disease, slipped capital femoral epiphysis, or developmental hip dysplasia (lateral center edge angle [LCEA] <20 $\lt 2{0}^{\circ }$).…”
Section: Methodsmentioning
confidence: 99%
“…The joint capsule acts as a non-dynamic stabilizer restricting the femoral head’s excessive translation and rotational movement [ 73 ••, 74 , 75 ]. Most commonly performed hip arthroscopy involves capsulotomy to gain access to the hip joint, with the most common techniques being interportal and T-shaped capsulotomies [ 74 , 76 , 77 ]. Further, in hip dysplasia, the capsule is generally lax and redundant due to the bony undercoverage and ongoing instability [ 3 •, 9 , 73 ••, 74 , 78 ].…”
Section: Arthroscopic Treatmentmentioning
confidence: 99%